Chronicles of England, France, Spain and the adjoining countries - Froissart, Jean 1337-1405; Johnes, Thomas (London Smith, 1839)
Froissart's CHRONICLES (or CHRONIQUES) was written in French by Jean Froissart, chronicling the years 1322 until 1400, and describing the conditions that created the Hundred Years' War, as well as the first fifty years of the war. For centuries it has been recognized as the chief expression of the chivalric revival of 14th century England
Ex libris Sir Ernest Cable (plate) & Frederick Richard Pickersgill (manuscript)
Translated from the french editions, with variations and additions from many celebrated mss. (...) to which are prefixed a life of the author, an essay on hus works, and a criticism on his history
Keywords: Middle Ages (500-1400); Hundred Years' War (1337-1453); History; Europe